A legitimidade da concessão judicial de medicamentos de alto custo na tutela individual: aspectos jurídicos, filosóficos e políticos - CASSEB, Ana Luísa Campos (Universidade Federal do Pará, 2018)
This work has as general objective to analyze the phenomenon of the judicialization of public health policies in Brazil, and for a particular purpose to reflect on the legitimacy of the judicial decisions that grant high cost drugs to individuals. The problem raised by these objectives is the following question: in what way can such decisions be considered as legitimate mechanisms of distributive justice, considering the legal, philosophical and political aspects of the legitimacy of such a circumstance? The present research supports the hypothesis that the three dimensions examined offer assumptions that are able to demonstrate the correctness of the redistributive act that occurs through these decisions. Thus, it is an eminently theoretical investigation, with an argumentative trait, since it seeks to contrast the existing positions on the subject in Brazilian constitutional law, in political philosophy, in the jurisprudence of the Federal Supreme Court, with special attention to the votes thus far in the judgment of Extraordinary Remedies no. 566.471/RN and 657.718/MG. As a result, after articulating the categories of the rule of law, equal opportunities and cooperative solidarity in the perspective of the right to health, this research is consolidated in order to affirm the justice in the redistributive practice of access to public health policies by judicial process